Free will and consciousness : a determinist account of the illusion of free will - Caruso, Gregg D. (Lexington Books, 2012)
This book argues two main things: The first is that there is no such thing as free will-at least not in the sense most ordinary folk take to be central or fundamental; the second is that the strong and pervasive belief in free will can be accounted for through a careful analysis of our phenomenology and a proper theoretical understanding of consciousness.